THE BIDIRECTIONAL IMPACT OF DIVIDENDS & LIQUIDITY ON NON BANKING COMPANIES IN INDONESIA FROM 2013 to 2023 - Yohana Febriani; Vina Nugroho (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study aims to determine the bidirectional influence between liquidity and dividends in non-banking public listed companies in Indonesia during 2013-2023. This study examines how dividends and liquidity affect each other, using ROE, firm size, solvency, book value, leverage, and investment variables as additional factors that can affect dividend and liquidity policies. The results show a mutual influence between dividend policy and liquidity. In addition, ROE, company size and solvency have a significant influence on dividends and liquidity.